Dynamics of He atoms adsorbed on a carbon nanotube - Strzhemechny, Mikhail A.; Legchenkova, Irina V. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2011)
The spectrum of a helium atom adsorbed on an armchair single-walled carbon nanotube is calculated. It is shown that a helium adatom tunnels over the surface of the nanotube within a band 10 K (for 4He) to 14 K (for 3He) wide. The undersaturated system of helium adatoms on nanotubes can be used as another system for studying quantum transport. It is also felt that this dynamics can be an important factor for the explanation of the large negative expansivities of nanotube bundles with adsorbed helium.